Analisis Tata Cara Validasi SSP atas Penghasilan dari Pengalihan Hak atas Tanah atau Bangunan di KPP Pratama Kosambi - Ramadhan Andriana, Rangga (Jurnal Etnik: Ekonomi-Teknik, 2023)
Taxes are mandatory contributions to the state that are owed by individuals or entities that are coercive based on the law, by not getting compensation directly and used for the needs of the state for the greatest prosperity of the people. One of the tax obligations that is prone to errors or fraud is when validating income from the transfer of rights over land and/or buildings inTax office Primary. This study aims to analyze the implementation of validationTax payment slipon income from the transfer of rights to land or buildings inTax office Primary Kosambi. Based on the author's interviews with implementers in the Service Section, the Integrated Service Center Section, during the 2017 to 2019 tax year Procedures for validationTax payment slip OfTax office Pratama Kosambi refers to the Regulation of the Director General of Taxes Number PER-18/PJ/2017. Even though in the 2019 tax year the regulations used were PER-26/PJ/2018, so there are differences in the application of the applicable regulations. validation procedureTax payment slip at the Kosambi Pratama Tax Service office refer to PER – 18/PJ/2017 for the 2017 to 2018 tax years and PER – 20/PJ/2019 for the 2020 tax year. The procedures implemented have been effective and efficient because it cuts processing time and taxpayers it is also easier in terms of completing the lack of files.